The prevalence of radiographic femoroacetabular impingement morphology in adolescent spine patients (Medicine Science, 2021)
Changes in spinal alignment may alter hip biomechanics and predispose hip pathologies. Only a few studies have examined the relationship between adolescent spinal deformities and femoroacetabular impingement syndrome of the hip. The purpose of this study is to define the prevalence of femoracetabular impingement radiographic findings among adolescent spine patients. We evaluated 230 hips of 115 patients with adolescent idiopathic scoliosis as a study group. One hundred hips of 50 volunteers were analyzed as a control group. Radiographic images were analyzed for anteroposterior alpha angle, Tonnis angle (TA), center-edge angle (LCEA), crossover sign (COS), ischial spine sign (ISS), coxa profunda (CP), pelvic incidence (PI), pelvic tilt (PT), sacral slope (SS), and lumbar lordosis (LL). Of the 330 hips, 57.3 % demonstrated at least one parameter suggesting impingement morphology, whereas 23% showed at least two parameters. Evidence of coxa profunda was seen in 35.5% of the hips, while a negative Tonnis angle was seen in 57.3% and a center-edge angle indicative of acetabular overcoverage was seen in 23%. An acetabular crossover sign was detected in 13.9% of the hips, while an abnormal anteroposterior alpha angle was found in 12.1% of the hips studied. Statistical analysis revealed that the radiographic signs of femoroacetabular impingement syndrome among adolescent scoliosis patients were significantly higher than the control group. There was a difference between the two groups for sacral slope (p [Med-Science 2021; 10(2.000): 524-8]